Comparison of stool versus rectal swab samples and storage conditions on bacterial community profiles - Christine M. Bassis (BMC Microbiology, 2017)
Abstract Background Sample collection for gut microbiota analysis from in-patients can be challenging. Collection method and storage conditions are potential sources of variability. In this study, we compared the bacterial microbiota from stool stored under different conditions, as well as stool and swab samples, to assess differences due to sample storage conditions and collection method. Methods Using bacterial 16S rRNA gene sequence analysis, we compared the microbiota profiles of stool samples stored and collected under various conditions. Stool samples (2 liquid, 1 formed) from three different patients at two hospitals were each evaluated under the following conditions: immediately frozen at -80°C, stored at 4°C for 12-48 hours before freezing at -80°C and stored at -20°C with 1-2 thaw cycles before storage at -80°C. Additionally, 8 stool and 30 rectal swab samples were collected from 8 in-patients at one hospital. Microbiota differences were assessed using the Yue and Clayton dissimilarity index (θYC distance) and analysis of molecular variance (AMOVA). Results Regardless of the storage conditions, the bacterial communities of aliquots from the same stool samples were very similar based on θYC distances (median intra-sample θYC distance: 0.035, IQR: 0.015-0.061) compared to aliquots from different stool samples (median inter-sample θYC distance: 0.93, IQR: 0.85-0.97) (Wilcoxon test p-value: <0.0001). For the stool and rectal swab comparison, samples from different patients, regardless of sample collection method, were significantly different (AMOVA p-values: <0.001-0.029) compared to no significant difference between all stool and swab samples (AMOVA p-value: 0.976). The θYC dissimilarity index between swab and stool samples was significantly lower within individuals (median 0.17, IQR: 0.10-0.27) than between individuals (median 0.93, IQR: 0.85-0.97) (Wilcoxon test p-value: <0.0001), indicating minimal differences between stool and swab samples collected from the same individual over the sampling period. Conclusion For gastrointestinal microbiota studies based on bacterial 16S rRNA gene sequence analysis, interim stool sample storage at 4 °C or -20 °C, rather than immediate storage at -80 °C, does not significantly alter results. Additionally, stool and rectal swab microbiotas from the same subject were highly similar, indicating that these sampling methods could be used interchangeably to assess the community structure of the distal GI tract.